Two-dimensional reconstruction of education based on maqasid al-shariah in Islamic boarding schools - Taufikin; Sanusi (Al'Adalah, 2026)
Integral education has regained prominence amid concerns that contemporary education usually separates academic achievement from moral, spiritual, and personal development. Within Islamic education, this issue is a theoretical one; embodied religious practices must be interpreted through both Indonesian educational philosophy and maqasid al-shariah, without reducing either framework to a prescriptive ideal. The present study examines the institutionalization of tirakat practices in two children’s pesantren in Central Java and analyzes their educational significance through the perspectives of Ki Hadjar Dewantara’s educational anthropology and contemporary maqāṣid scholarship. A qualitative multiple-case study was conducted over two years, employing observations, in-depth interviews with 22 students, 2 kiai, and 10 teachers, and analysis of institutional documents. Data were analyzed using reflexive thematic analysis and abductive interpretation. The results show that fasting, tahajud, wirid, and tahfidz al-Qur’an are interconnected practices that foster bodily discipline, spiritual internalization, self-regulation, ethical awareness, and holistic development. These themes correspond analytically with the five dimensions of maqasid al-shariah. The study puts forward the Integral Maqasid-Based Dual Formation Model as a contextually grounded conceptual framework, supported by empirical evidence and developed through interpretive analysis. Future research needs to evaluate its applicability across different age groups, pesantren traditions, and educational contexts.